Factors Involved in Nurses' Health-Seeking Behaviors: A Qualitative Study. (5th January 2023) - Najafi, Tahereh; Rafii, Forough; Rahimi, Sara
Abstract : This study aimed to explore the factors involved in Iranian nurses' health-seeking behavior. In this qualitative exploratory descriptive study, 15 nurses from hospitals affiliated to Iran and Qazvin University of Medical Sciences were interviewed from April to March 2020. Data were collected via purposive sampling by unstructured in-depth interviews and analyzed using thematic analysis. Findings identified 5 main themes, "fear, " "trust/distrust, " "excuse, " "accessibility, " and "support" that were involved in nurses' health-seeking behavior. The findings of this study may contribute to a deeper understanding of the factors involved in nurses' health-seeking behavior and pave the way for further research and policy making regarding nursing workforce health.